Cover Feature: Ultrafast Charge Dynamics in Mixed Cation – Mixed Halide Perovskite Thin Films (ChemPhysChem 22/2018). Issue 22 (8th November 2018) - Minda, Iulia; Horn, Jonas; Ahmed, Essraa; Schlettwein, Derck; Schwoerer, Heinrich
Abstract : The Cover Feature shows the ultrafast charge dynamics which occur upon photoexcitation of a mixed‐halide – mixed‐cation lead‐based perovskite thin film depicted together with the spectroscopic signatures obtained from femtosecond transient absorption spectroscopy. A diagram of the perovskite structure and its chemical composition is shown alongside. More information can be found in the Article by I. Minda et al. onpage 3010 in Issue 22, 2018 (DOI:10.1002/cphc.201800547 ).